Stability and displacement analysis of interlayered soft-hard slopes under seismic loading - Chuxiang Feng; Yong Yin (Scientific Reports)
Abstract The stability and displacement response of soft-hard interbedded slopes under seismic loading are crucial in seismic geotechnical engineering. This study investigates the dynamic behavior of slopes composed of alternating hard and soft rock layers using FLAC3D with a Mohr–Coulomb constitutive model and the strength reduction method. Through a series of numerical simulations involving varying seismic intensities (0.1 g, 0.3 g, 0.5 g) and structural parameters such as slope angle, dip angle, rock strength ratio, and soft-hard thickness ratio, the effects on slope stability and displacement were analyzed. Under static conditions, the calculated safety factor (Fs) ranged from 1.69 to 6.42 across 15 slope models. Simulation results revealed that as the strength parameter k and hard-rock proportion increased, slope stability improved. Under dynamic loading, the safety factor showed a decreasing trend with increasing seismic acceleration. For example, in No.5 model, the safety factor decreased from 6.42 (static) to 4.86 (0.1 g), 3.21 (0.3 g), and 2.10 (0.5 g). Displacement time histories showed that horizontal displacements increased significantly with seismic intensity, with Point E recording a peak horizontal displacement exceeding 0.2 m under 0.5 g. Meanwhile, vertical displacement differentiated between slope top uplift and foot settlement, indicating interlayer shear-slip behavior. The results provide theoretical support for seismic-resistant design of interbedded rock slopes, emphasizing the need for enhanced support in high-intensity earthquake zones.